Adverse health effects in humans exposed to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) - Pelclová, Daniela; Urban, Pavel; Preiss, Jan; Lukás, Edgar; Fenclová, Zdenka; Navrátil, Tomás; Dubská, Zora; Senholdová, Zdenka (Reviews on environmental health, 2006)
The environmental contaminant 2,3,7,8-tetrachlordibenzo-p-dioxin (TCDD) belongs to the category of highly toxic, persistent organic pollutants that accumulate in animal fat and plant tissues. Today, background TCDD levels in human fat are showing a decreasing trend. The food chain is the main source of exposure in the human population. TCDD regulates the expression of a wide range of drug-metabolizing enzymes and has an impact on a large number of biological systems. The most pronounced effects have occurred in occupational settings following the uncontrolled formation of TCDD after industrial accidents, as well as in rare intentional intoxications. Although the acute effects of TCDD exposure are well described in the literature, the long-term consequences have been underevaluated. The most well-known symptoms of severe acute intoxication are chloracne, porphyria, transient hepatotoxicity, and peripheral and central neurotoxicity. Because of the long-term persistence of TCDD in the human body, atherosclerosis, hypertension, diabetes, vascular ocular changes, and signs of neural system damage, including neuropsychological impairment, can be present several decades after massive exposure. Such chronic effects are nonspecific, multifactorial, and may be causally linked to TCDD only in heavily intoxicated subjects. This opinion is supported by the dose-dependent effect of TCDD found in exposed workers and by experimental animal studies.
Keywords: látky znečišťující životní prostředí; Diabetes Mellitus; Nervous System Diseases; Environmental Exposure; vystavení vlivu životního prostředí; Environmental Pollutants; polychlorované dibenzodioxiny; Eye Diseases; ateroskleróza; Humans; diabetes mellitus; lidé; hypertenze; oční nemoci; Atherosclerosis; Polychlorinated Dibenzodioxins; Hypertension; nemoci nervového systému